La patologia mentale in carcere. Note sulla diagnosi, la terapia e la cura nell’istituzione penitenziaria - Ponti, Massimo; Carlotto, Alessandra (Il sogno della farfalla, 2014)
Facing mental pathology in prison means identifying a particular dynamic, i.e. acting-out. The authors begin by considering the legislation that governs the treatment of prisoners with mental problems and the different categories linked to mental infirmity, to then undertake a critical analysis of the different points of view of the judiciary and forensic psychiatry in relation to the mental patient, highlighting the difference between being bad/evil and being ill and the way this is experienced in modern society and culture. After having considered a clinical case the authors describe the different pathologies linked to the prison world (such as the phenomenon of prisonization and the Ganser syndrome) and in closing they analyze the risk of suicide within the prison population not only among the detainees, but also with respect to the prison staff.